Magnesium‐dependent activated partial thromboplastin time assay—Simple method for lupus anticoagulant detection - Tokutake, Takayoshi; Ieko, Masahiro; Naito, Sumiyoshi; Yoshida, Mika; Baba, Hisami; Kobayashi, Hikaru; Ishida, Fumihiro (International journal of laboratory hematology, 2020)
Introduction Detection of lupus anticoagulant (LA), an antiphospholipid (aPL) antibody, in a clotting time test is an important finding for diagnosis of antiphospholipid syndrome (APS). However, confirmation of LA requires several different testing procedures, some of which can be difficult and require time. We report here a simple and highly specific method for detecting LA. Materials and Methods We examined 66 plasma samples obtained from LA‐positive (LA) and 75 from LA‐negative (non‐LA) subjects, which included patients with acquired hemophilia and coagulation disorders, as well as from 43 healthy volunteer samples as normal controls. Activated partial thromboplastin time (APTT) was determined by adding 20 mmol of CaCl2 (Ca‐APTT) or 25 mmol of a mixture of Mg and Ca (Mg‐APTT). The ratio of Mg‐APTT/Ca‐APTT was then calculated and used as the Mg/Ca Index. Results The Mg/Ca Index value for the LA group was significantly lower than that for the non‐LA and normal control groups (P < .0001). When the cutoff value of the Mg/Ca Index was less than 1.00, the sensitivity of LA determination using the Mg‐APTT assay was 80.3%, while specificity was 100%. Conclusion Our findings indicate that the present Mg‐APTT assay is a simple yet highly specific method for LA detection.